Non-classical mnemonic actors and new commemorative practices in the network space - I. S. Soldatenko (Вестник университета)
The research focuses on non-classical mnemonic actors – video bloggers and creators of computer games. As part of the study of new commemorative practices, we consider video blogs focused on historical topics, internet memes of historical orientation, and computer games aimed at representing the past. The purpose of the article is to analyse the specifics of the activities of the non-classical mnemonic actors in the translation of historical narratives and specifics of the implementation of modern commemorative practices. The research uses the achievements of memory studies, meme studies, and game studies. The article consists of an introduction, description of the main research results, and conclusion. The article concludes about the influence of algorithms of popular platforms on the formation of collective memory. An attempt is made to identify a number of features that characterise the activity of the non-classical mnemonic actors in the network space. The features include active depersonalisation of some new mnemonic actors, their active use of certain types of social network interaction in their activities. The specifics of new commemorative practices in the online space are revealed, among which partial democratisation of the mnemonic field stands apart. Recommendations are given on the development of computer games with a historical plot.